Relationship between Divergent Thinking and Digital Literacy on Teacher Ability to Develop HOTS Assessment - Widana, I Wayan; Ratnaya, Gede (Journal of Education Research and Evaluation, 2021)
The low ability of high/vocational school mathematics teachers to develop HOTS assessments is a serious problem that must be immediately found a solution to be able to increase student competitiveness in the 21st century. This study aims to analyze the relationship between divergent thinking and the ability of teachers to develop HOTS assessments, the relationship between digital literacy and teachers' abilities to develop HOTS assessments, and the relationship between divergent thinking and digital literacy with teachers' abilities to develop HOTS assessments. This research is a quantitative non-causal survey method. The research design used a correlational regression model. The study population was high school/vocational high school mathematics teachers in Bali, NTB, and NTT. The sample selection used the cluster random sampling technique. Research data were collected using a questionnaire. Data were analyzed using multiple linear regression assisted by SPSS 23.0 for Windows. The results show a significant positive relationship between divergent thinking and the ability of teachers to develop HOTS assessments. There is a significant positive relationship between digital literacy and teachers' abilities to develop HOTS assessments. There is a significant positive relationship between divergent thinking and digital literacy and the teacher's ability to develop a HOTS assessment.